Education of Pedagogical Technologies in the Formation of Knowledge, Skills, Qualifications of Students (Journal of Pedagogical Inventions and Practices, 2023)
This article explores the transformative role of pedagogical technologies in enhancing the knowledge, skills, and qualifications of students, with a specific emphasis on the innovative Ahmadiyya approach. The article provides insights into the methods, results, and implications of using Ahmadiyya pedagogical technologies and their potential to revolutionize modern education